1986
DOI: 10.1128/mcb.6.6.2233
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for free and metabolically stable p53 protein in nuclear subfractions of simian virus 40-transformed cells.

Abstract: To determine functional subcellular loci of p53, a cellular protein associated with cellular transformation, we analyzed the nucleoplasmic, chromatin, and nuclear matrix fractions from normal mouse 3T3 cells, from methylcholanthren-transformed mouse (MethA) cells, and from various simian virus 40 (SV40)-transformed cells for the presence of p53. In 3T3 and MethA cells, p53 was present in all nuclear subfractions, suggesting an association of p53 with different structural components of the nucleus. In 3T3 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
0
3

Year Published

1987
1987
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 30 publications
6
46
0
3
Order By: Relevance
“…This view was supported by experiments described by Linzer et al (17) which demonstrated that metabolic stabilization of p53 depends on the expression of a functional large T. However, formation of a p53 complex with a transforming protein could not explain the increase in metabolic stability of p53 in many other transformed cells: except for formation of complexes with large T of SV40 and several other papovaviruses (for a review, see reference 3) and with the adenovirus Elb 58K tumor antigen (33), no other complexes of p53 with viral or cellular transforming proteins have been reported. Furthermore, we have provided evidence that SV40-transformed cells also contain p53 molecules which are not complexed to large T (free p53) but are metabolically stable, like p53 in non-SV40-transformed cells, e.g., MethA cells (5). This finding suggested that at least the free p53 in SV40-transformed cells might become stabilized by a cellular process.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…This view was supported by experiments described by Linzer et al (17) which demonstrated that metabolic stabilization of p53 depends on the expression of a functional large T. However, formation of a p53 complex with a transforming protein could not explain the increase in metabolic stability of p53 in many other transformed cells: except for formation of complexes with large T of SV40 and several other papovaviruses (for a review, see reference 3) and with the adenovirus Elb 58K tumor antigen (33), no other complexes of p53 with viral or cellular transforming proteins have been reported. Furthermore, we have provided evidence that SV40-transformed cells also contain p53 molecules which are not complexed to large T (free p53) but are metabolically stable, like p53 in non-SV40-transformed cells, e.g., MethA cells (5). This finding suggested that at least the free p53 in SV40-transformed cells might become stabilized by a cellular process.…”
mentioning
confidence: 61%
“…A detailed description of the cell fractionation procedure, as well as a characterization of extracts and structures, has been given elsewhere (11,(34)(35)(36). Briefly, cells grown on petri dishes (9 cm) were washed with KM buffer [10 mM morpholinepropanesulfonic acid (MOPS; pH 6.8), 10 mM NaCl, 1.5 mM MgCl2, 1 mM ethylene glycol-bis(,B-aminoethyl ether)-N,N, N',N'-tetraacetic acid (EGTA), 5 (5,35).…”
mentioning
confidence: 99%
“…Similarly, p53 in complex with the adenovirus 58-kilodalton (kDa) Elb protein is also very stable (38,44). Nevertheless, there is growing evidence that at least part of this stabilization may be due to indirect effects of the viral transformation rather than simply to the tight association between the proteins (10,11,44).…”
mentioning
confidence: 99%
“…First, p53 turnover decreases in adenovirus type 12-transformed cells, even though the protein does not form a stable, immunoprecipitable complex with Adl2 p55 ~m (Zantema et al 1985). Second, the half-lives of free and T antigen-associated p53 are similar in SV40-transformed cells (Deppert and Haug 1986). In both cases, the effect of the tumor antigen on p53 turnover was attributed to metabolic changes associated with cell transformation, although neither study excluded the possibility of physical interactions between the tumor antigen and p53.…”
mentioning
confidence: 99%